Parenting Styles and Disordered Eating Among Youths: A Rapid Scoping Review - Hampshire, Chloe; Mahoney, Bérénice; Davis, Sarah K. (Frontiers in Psychology, 2022)
Youth is a critical period in the development of maladaptive eating behaviours. Previous systematic reviews suggest the aetiological significance of parent-child relationships for the onset of disordered eating in youth, but less is known about the role of parenting styles. This rapid scoping review aimed to identify whether research supports the role of parenting styles in the development of disordered eating symptoms among youths. 16 studies, retrieved from three databases (PsycArticles, PsycInfo and BASE), met the inclusion criteria: original studies, published in English, examined the effect of parenting styles (authoritative or neglectful) on cognitive (drives for thinness and body dissatisfaction) and behavioural (weight control behaviours) disordered eating outcomes, among young people up to 18 years of age. Studies supported an association between various youth disordered eating symptoms such as unhealthy weight control behaviours, and experiences of adverse parenting styles characterised by high levels of control and low levels of responsiveness. Associations between adverse parenting styles and youth disordered eating were frequently indirect and differed depending on the sex of the parent and offspring. Synthesis of findings was limited due to variation in the operationalisation and measurement of parenting styles, family context and disordered eating across studies. Longitudinal and standardised research is required to better understand the dynamic associations between parenting styles and youth disordered eating. Implications for family-based care in clinical practise are discussed.